PENYELENGGARAAN PELAYANAN AKTA PADA DINAS KEPENDUDUKAN, DAN CATATAN SIPIL KABUPATEN BOYOLALI - MULYANI, SRI (Dinamika Hukum, 2017)
The purpose of this research is to study and analyze whether the implementation of birth certificate service in the Department of Population and Civil Registration (Dinas Kependudukan dan Catatan Sipil) of Boyolali Regency had been appropriate to the legal provisions and to study and analyze the acceleration in the service of the civil document ownership in the Department of Population and Civil Registration in Boyolali Regency. Background of this research focus is the service function in the hand of the Department of Population and Civil Registration as a government bureaucracy more focuses on the creation of a civil administration order especially related to the legal position of the citizen in the forms of civil registration certificates. The needs on the data of legal position of citizen which is in the forms of of civil registration certificates is very important for the legal certainty. This research used the type of a juridical normative research. The location selected is the Office of the Department of Population and Civil Registration in Boyolali Regency. The characteristics of this research is descriptive which is according to Soerjono Soekamto is â€œa research which provides an initial data as carefully as possible about human, condition or other symptomsâ€. Object of the research is the Implementation of Birth Certificate Service in The Department of Population and Civil Registration of Boyolali Regency. The data were obtained from some information or facts directly from the Head of the Office, the Head of the Division, the Head of Sub-division, the Head of Section, and the Officers of Service Executor. The results of the research showed that the implementation of birth certificate service in the Department of Population and Civil Registration had been appropriate to the Act Number 24 of 2013 regarding the Amendment of Act Number 26 which regulates the civil administration because it had increased the civil service. It was directed toward the activities of increase in the public service in the civil field and increase in infrastructure of civil service. The acceleration of the service of civil document ownership of the civil administration is for creating the order of Civil Administratin by the establishment of civil database nationally as well as the validity and the correctness of the civil document issued. Keywords: administration order and civil document.